Gadolinium deposition in the liver and brain in a rat model with liver fibrosis after intravenous administration of gadoxetate disodium - Peiying Wei; Qiuhui Hu; Chengbin He; Peng Hua; Di Yang; Chang Shao; Lesi Xie; Zhijiang Han; Xiaoxuan Zhou; Zhongxiang Ding; Hongjie Hu (Heliyon, 2024)
Objectives: To investigate gadolinium deposition in the liver and brain in a rat model with liver fibrosis (LF) after intravenous administration of gadoxetate disodium (GD) and the histological effects of gadolinium deposition in the liver and brain. Methods: Adult male Sprague–Dawley rats were randomly assigned to one of the three groups: 1) LF group received intraperitoneal injection of carbon tetrachloride (CCl4) for 9 weeks alone; 2) LF&GD group received CCl4 and intravenous administration of GD (for 5 consecutive days); 3) GD group received olive oil and GD. Seven days after the final injection of GD, the deep cerebellar nuclei (DCN) and liver were excised to determine gadolinium concentrations via inductively coupled plasma mass spectrometry, and histologic staining was performed. Bonferroni's post-hoc test and Wilcoxon rank sum test were used to compare the differences between the three groups. Results: The concentrations of retained gadolinium in the liver in the LF&GD group (2.18 ± 0.44 μg/g) were significantly greater compared to the LF group (0.02 ± 0.01 μg/g, P < 0.001) and GD group (0.37 ± 0.11 μg/g, P < 0.001). Also, the concentrations of retained gadolinium in DCN were increased in the LF&GD group (0.13 ± 0.06 μg/g) compared to the LF group (0.01 ± 0.00 μg/g, P < 0.001) and GD group (0.06 ± 0.02 μg/g, P = 0.019). No histopathological alterations were detected in the liver and DCN between LF&GD group and LF group. Conclusions: LF aggravated gadolinium deposition in the liver and DCN after administration of GD. However, no significant acute histological alterations were observed due to gadolinium deposition.